(untitled) (Jurnal Bahasa, 2018)
This paper aims to analyse the progressive verb "sedang" for the class of achievement predicates in the Malay language. Progressive verbs accord a role to a word which expresses an action or process, it could also appear naturally with verbs which express a state (thoughts, emotions etc). In the Malay language, a marker that refers to the act of ongoing and incomplete action is normally indicated by an auxiliary verb progressive aspect for example "sedang" and "tengah" (colloquial form of "sedang") and "masih". However, this study focuses only on the progressive verb "sedang" in order to determine the class of achievement predicates. Essentially, the class of achievement predicates refers to the instantaneous change of a certain state. In an instantaneous condition, a change could create a new state. Thus, the class of achievement predicates is marked as an act which has an inherent endpoint. Generally, a class of achievement predicates describes the instantaneous change of a certain state to a new one. This study benefited from the database of Dewan Bahasa dan Pustaka, and the data were analysed using the concept of semantic theory, Van Valin’s role and reference grammar (RRG) and Rothstein’s approach (2004). Previous researchers explained that it is not possible for the progressive verb "sedang" to exist with the class of achievement predicates. However, the corpus generation challenges the above mentioned claim. Keywords: progressive verb "sedang", achievement predicates, role and reference grammar theory, corpus data, the Malay language